The efficacy of metformin and exenatide in Polycystic Ovary Syndrome (PCOS) patients - Kesavan, Sanggeeta; Chaudhry, Gul-e-Saba; Md Akim, Abdah; Ranneh, Yazan K (Universidad de Granada, 2023)
Introduction: Polycystic Ovary Syndrome (PCOS) is a hormonal disorder that affects 5-10% of women who are their reproductive age. This meta-analysis aims to evaluate the efficacy of metformin and exenatide, respectively, and to compare the efficacy of both drugs using Body Mass Index (BMI), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and testosterone level. Method: Scopus, Science Direct, Oxford Journal, Wiley Online Library, and Medline (through the PubMed search engine) were used in this study. Statistical analysis of the included studies was done using the RevMan 5.4 software. Results: There were 6 studies included in the analysis of the study. There was a significant reduction in BMI of PCOS patients with exenatide versus metformin (mean difference = 0.51; 95% confidence interval (CI)= 0.07, 0.96, I 2= 52%; p=0.02). There was also a significant reduction in the testosterone level of PCOS patients with exenatide versus metformin (mean difference = 0.15; 95% confidence interval (CI)= 0.07, 0.22, I 2= 0%; p=0.0002). There was no effect on the mean of LDL-C and of HDL-C when compared between metformin and exenatide This meta-analysis shows that exenatide is effective in reducing BMI and testosterone levels in PCOS patients. Conclusions: There were a significant reduction in BMI and testosterone levels of PCOS patients when exenatide was used as compared to metformin. However, there was no effect on the mean of the LDL-C and HDL-C levels of the PCOS patients.